Stages of the shaping the physical culture to personalities - Кутек [Kutek T.] Т. Б. (Slobozhanskyi Herald of Science and Sport, 2013)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–> On the basis of the conducted research the basic stages of forming of physical culture of personality are certain. It is set that the stages of forming of physical culture of personality the features among which is underlaid: heredity, education, studies, terms of dwelling, physical development, level of physical preparedness, formings of requirement, is in the healthy method of life, knowledge and understanding of role of physical culture, for development of personality, confession of physical culture as social’nolichnostnoy value. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>